2018
DOI: 10.18488/journal.61.2018.64.239.252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Utilizing the STAD Method (Cooperative Learning Approach) in Enhancing Students Descriptive Writing Skills

Abstract: Article HistoryKeywords STAD method Descriptive writing ESLwriting Action research Year six students International school.Students" ESL writing skills in general are not at a desirable level. The objective of this study was to determine the effectiveness of utilizing the STAD method to enhance descriptive writing skills among students in an international school in Selangor, Malaysia. This study employed an action research design. The sample consisted of 20Year 6 students aged between 11 and 12 years. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 7 publications
6
18
0
Order By: Relevance
“…In addition to the general writing skills including the choice of vocabulary, sentence structure, grammar and mechanics ( Nair and Sanai, 2018 ; Chen et al, 2019 ), there are some descriptive techniques commonly used in Chinese landscape literature. The advocated descriptive writing techniques has been listed in the curriculum guide.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the general writing skills including the choice of vocabulary, sentence structure, grammar and mechanics ( Nair and Sanai, 2018 ; Chen et al, 2019 ), there are some descriptive techniques commonly used in Chinese landscape literature. The advocated descriptive writing techniques has been listed in the curriculum guide.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These skills can also affect one's responses, attitudes, and actions to think broadly (Alrfooh, 2014). These skills should be habituated since elementary school age, so the students can compete to face various problems (Nair & Sanai, 2018). Everyone's creativity or divergent-thinking skill is closely related to their future in being able to give different ideas, innovate, easily develop, and adapt to the environment (Akcanca & Ozsevgec, 2019).…”
mentioning
confidence: 99%
“…Studies conducted by Johnson and Johnson (1985); Fletcher (2006); Periasamy (2011) showed that the utilization of the STAD method to enhances students" reading skills. A study by Nair and Sanai (2018) indicated that the STAD method enhances students" descriptive writing skills. Similarly a study conducted by Gambari and Yusuf (2015) among Nigerian students indicated that students taught physics using computer -assisted STAD performed significantly better than the control group.…”
Section: Stad Methodsmentioning
confidence: 99%